DETERMINAN STRUKTUR MODAL PADA SEKTOR PROPERTY, REAL ESTATE DAN CONTRUCTION DI BURSA EFEK INDONESIA - Shafly Perdana Lestamanta; Elok Sri Utami; Lilik Farida (BISMA: Jurnal Bisnis dan Manajemen, 2022)
This study investigates the determinants of capital structure policy in the property, real estate, and construction sectors on the Indonesia Stock Exchange. The unit of analysis is financial reports. The sampling technique using purposive sampling method uses the criteria the company does not have negative profits and does not carry out mergers/acquisitions during the 2012-2018 research period; a sample of 224 is obtained. The method of analysis is multiple linear regression analysis. The results showed that the variables profitability, earning volatility, growth opportunity, and size had a positive effect on capital structure. In contrast, the variables of responsibility and non-debt tax shield did not affect capital structure.